P272 Management of fingertip injuries in the paediatric emergency department clinic- more than local anaesthesia. (June 2019) - Egan, Aileen; Cullen, Deborah; Fitzpatrick, Patrick
Abstract : Trauma and injuries represent a significant portion of presentations to the Paediatric Emergency Department, with a major subset comprising hand and fingertip injuries. These require input from specialist hand surgeons. In co-ordinating this care pathway, the aim is to provide effective and definitive treatment in a manner that is straightforward for parents and least stressful for the injured child. Frequently, these injuries are suitable for repair under local anaesthesia. In the presence of a well-stocked treatment room, repair of simple fingertip injuries can be facilitated, avoiding the need for full hospital admission and prolonged fasting for repair under general anaesthesia. Our study evaluated all fingertip and nailbed injuries presenting to our Emergency Department in an 8 month period from January to August 2018. Out of 964 presentations for Plastic Surgery review, 226 concerned hand or finger injuries. Of these, 140 represented fingertip or nailbed injuries. Almost 40% of these underwent repair in the Emergency Department under local anaesthesia with or without nitrous oxide sedation. 25% required repair in the operating theatre under general anaesthesia and 35% were managed conservatively. August was the busiest month for such injuries. Children undergoing nitrous sedation with local anaesthesia for these injuries ranged from 15months to 14 years, with a median of 4 years. In general, younger babies and more anxious or upset children were less suitable for sedation and local anaesthesia. All cases were followed up routinely in the Plastic Surgery clinic. Side effects of nitrous sedation were uncommon. There were almost no complications following these procedures. This audit provides a snapshot of the usefulness of nitrous sedation in combination with local anaesthesia as a safe and reproducible method of managing simple fingertip injuries in the paediatric setting. It highlights issues around provision for these services in the Emergency Department- staffing, equipment and training to name but some- but will surely assist in future resource planning.